2018
DOI: 10.3390/ijerph15050851
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Translated Disease Self-Management Program on Employee Health and Productivity: Six-Month Findings from a Randomized Controlled Trial

Abstract: Disease management is gaining importance in workplace health promotion given the aging workforce and rising chronic disease prevalence. The Chronic Disease Self-Management Program (CDSMP) is an effective intervention widely offered in diverse community settings; however, adoption remains low in workplace settings. As part of a larger NIH-funded randomized controlled trial, this study examines the effectiveness of a worksite-tailored version of CDSMP (wCDSMP [n = 72]) relative to CDSMP (‘Usual Care’ [n = 109]) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…SNSs addiction increases task distraction of nurses on one hand as they are unable to concentrate on their work, while on the other hand, it reduces their organizational performance. However, if the nurses are self‐aware and can manage themselves, they can still neutralize the bad effects of SNSs addiction on their performance (Smith et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…SNSs addiction increases task distraction of nurses on one hand as they are unable to concentrate on their work, while on the other hand, it reduces their organizational performance. However, if the nurses are self‐aware and can manage themselves, they can still neutralize the bad effects of SNSs addiction on their performance (Smith et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies compared implementation strategies (e.g., different training, technology innovations to enhance provider uptake of the intervention) used to promote the uptake of CDSMP. 5 Implementation studies found that partnerships with community services organizations facilitated the program's further spread. 6 These implementation approaches vastly increased CDSMP's overall reach nationally in the USA, 7 though with mixed results internationally.…”
Section: Patient Education In Chronic Disease Managementmentioning
confidence: 99%
“…Success has also been reported using workplace interventions, which have resulted in improvements in activity and nutrition compared with control [114]. In Delhi, a multifactorial six-month worksite intervention focusing on education resulted in improvements in HDL-C, TG and WC compared with control groups [115].…”
Section: Preventionmentioning
confidence: 99%